3.1 Prediction of Fetal Compromise: The Use of Fetal Doppler Assessment in Normal Pregnancies Prior to Labour. (26th April 2013) - Prior, T; Mullins, E; Bennett, P; Kumar, S
Abstract : Introduction: Up to 63% of cases of intra-partum hypoxia occur in pregnancies with no antenatal risk factors. Identification before labour of these antenatally normal fetuses at risk of intra-partum hypoxia would enable a more targeted approach to intra-partum care. Methods: Five hundred and eleven women with uncomplicated, term, singleton pregnancies, underwent a pre-labour ultrasound assessment. This included measurement of fetal biometry, Umbilical artery, Middle cerebral artery, and Umbilical venous resistance indices. Clinicians managing the labour were blinded to the ultrasound results. Following delivery, case notes were reviewed and intra-partum outcomes correlated with ultrasound findings. Results: Infants born by Caesarean section for presumed fetal compromise had the highest Umbilical artery pulsatility index (p = 0.002), the lowest Middle cerebral artery pulsatility index (p < 0.001), the lowest cerebro-umbilical ratio (p < 0.001), the lowest Umbilical venous flow rates (p = 0.003), and the highest cerebral blood flow of any mode of delivery group (p = 0.007). A cerebro-umbilical ratio <10th centile has a positive predictive value of 36% for Caesarean section for presumed fetal compromise. This can be improved to 61.5% by inclusion of the other Doppler parameters. A cerebro-umbilical ratio >90th centile has a 100% negative predictive value. Conclusion: Pre labour fetal Doppler assessment can identify fetuses at both high and low risk of subsequent compromise in labour. Current intra-partum monitoring has a high false positive rate, which could be improved by better risk stratification prior to labour. This technique is easily translatable into clinical practise and would allow risk stratification of normal pregnancies prior to labour, enabling a more targeted approach to intra-partum care.